Youth Attitudes Toward Tourist Village Management in East Flores Archipelago - Saniamosenai, Klaudia Molasiarani; Fatchiya, Anna; Hapsari, Dwi Retno (Penerbit Goodwood, 2025)
Purpose: This study aims to 1) describe youth attitudes toward tourist village management and 2) analyse the factors influencing these attitudes. Methodology/approach: This study employs a mixed-methods approach, primarily quantitative with qualitative support. Using purposive sampling, we selected 71 respondents meeting the following criteria: aged 17-45 years, current residency status (non-travelers), employment status (working or unemployed), marital status (unmarried). Results/findings: The study revealed three key findings: 1) Youth attitudes toward tourism village business management were generally positive, with the affective dimension being most prominent; 2) Five factors significantly influenced these attitudes: individual characteristics, entrepreneurial traits, social learning, environmental support, and motivation. These factors collectively explained 49.4% of the variance in youth attitudes. Conclusions: Although youth maintain positive beliefs and evaluations regarding tourist village business management, this does not necessarily translate into their intention to engage in more formal contexts. Other determining factors come into consideration, including potential benefits and work flexibility. Limitations: This study does not account for tourism village infrastructure conditions, which may be significant predictors of youth attitudes toward tourism village business management. The quantitative design may overlook nuanced motivational factors. We recommend that future research employ FGD to examine youth motivations in greater depth qualitatively. Contribution: The village government can implement a two-pronged strategy to foster youth entrepreneurship: 1) Establish Village Youth Business Groups, 2) Create Experiential Learning Opportunities. This approach combines structural support with social learning, increasing capability and motivation.